The Effects of Exchange Rate Fluctuation on Bangladeshi Exports: An ARDL Bound Testing Technique - Khan, Md. Monir; Ahmed, Asif (International Journal of Economics and Financial Issues, 2024)
The objective of this paper is to investigate the influence of fluctuations in exchange rates on the export performance of Bangladesh. The analysis is based on annual data obtained from reputable sources such as the World Development Indicators (WDI) for the period spanning from 1981 to 2022. Autoregressive Distributive Lag (ARDL) bound testing approach is used to estimate the long-term as well as short-term relationship between the independent variables and dependent variable. The exports serve as the dependent variable, while the real exchange rate, gross capital formation (as a proxy for investment), inflation, and real interest rate are considered as the independent factors. The study’s findings suggest that Bangladesh’s exports are negatively impacted by exchange rates over the long and short terms. However, it is noteworthy that the magnitude of this negative effect is much greater in the long run as compared to the short run. Other controlled variables such as gross capital formation and real interest rate also have negative impact on exports in Bangladesh at lag one. Finally, this study suggests the implementation of policies that will foster better exchange rate stability as well as the pursuit of a stable and sustainable exchange rate policy.